Measuring Lifebuoy Ad Exposure in Building Awareness of KlikDokter Application Users during Pandemic COVID-19 - Halim Agung; Rustono Farady Marta; Vina Virshella (COMMUNICATION MAJOR, 2021)
Abstract The COVID-19 pandemic is a disease outbreak that makes almost all humans unable to travel freely, especially in Indonesia. Lifebouy and KlikDokter as one of the health products that have strong relevance related to preventive measures for the spread of this virus in Indonesia are the focus of researchers. This study aims to analyze exposure to lifebouy advertisements in building brand awareness of KlikDokter application users during the current pandemic. Data analysis used IBM SPSS Statistics 26 and involved 107 samples using the positivism paradigm, quantitative approach, survey methods, and data collection instruments in the form of questionnaires. The results of this research shows that the significance value is less than 0.05 which indicates that optimizing advertising exposure on various digital channels is a top priority in an effort to encourage user awareness in the use of a health service application.Keywords: advertising exposure; brand awareness; COVID-19; KlikDokter; Lifebuoy, survey.Abstrak Pandemi COVID-19 merupakan wabah penyakit yang membuat hampir seluruh manusia tidak dapat bebas berpergian terutama di Indonesia. Lifebouy dan KlikDokter sebagai salah satu produk kesehatan yang memiliki relevansi kuat terkait upaya preventif penyebaran virus di Indonesia menjadi fokus peneliti. Penelitian ini bertujuan untuk menganalisis terpaan Iklan Lifebouy dalam membangun kesadaran merek pengguna aplikasi KlikDokter di masa pandemi saat ini. Analisis data menggunakan IBM SPSS Statistics 26 dan melibatkan 107 sampel dengan menggunakan paradigma positivisme, pendekatan kuantitatif, metode survei, dan instrumen pengumpulan data berupa kuisioner. Hasil dari penelitian ini menunjukkan bahwa nilai signifikansi lebih kecil dari 0.05 yang menunjukkan bahwa optimalisasi terpaan iklan di berbagai saluran digital menjadi prioritas utama dalam upaya mendorong kesadaran pengguna dalam penggunaan suatu aplikasi layanan kesehatan.Kata Kunci: COVID-19; terpaan iklan; kesadaran merek; KlikDokter; Lifebouy; survei.